THE INFLUENCE OF LIQUIDITY, EARNING VARIABILITY, AND FIRM SIZE ON SYSTEMATIC RISK WITH PROFITABILITY AS MODERATION IN LQ45 COMPANIES IN 2020 – 2023 - Fajar Lazuardi, Muchammad; Ria Retnasih, Nora (Universitas Islam Lamongan, 2024)
The objective of this study is to examine the impact of liquidity, earning variability, and firm size on systematic risk in LQ45 enterprises from 2020 to 2023, with profitability as a moderating factor. The objective of this study is to analyse the impact of liquidity, earning variability, and firm size on systematic risk, while considering profitability as a moderating factor, inside the LQ45 enterprises during the period of 2020-2023. This study employs a quantitative research methodology. The population under study consists of the LQ45 firms, with a sample size of 29 companies. The analysis method is Moderating Regression Analysis (MRA). The research findings indicate that liquidity, earning variability, and Firm Size exert a substantial negative impact on systematic risk. Additionally, profitability has the potential to mitigate the influence of liquidity, earning variability, and Firm Size on systematic risk.